2009
DOI: 10.1002/mds.22114
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 49 patients with psychogenic movement disorders in a tertiary clinic in Turkey

Abstract: Patients admitted to movement disorders outpatient unit at a university hospital between January 2002 and June 2007 were screened for psychogenic movement disorders (PMDs). Out of 1,743 patients, 49 patients (2.8%), including four children, were diagnosed to have PMDs. Women to men ratio was 34/15. The mean age and the age-at-onset were 41 +/- 17 years and 36 +/- 15 years in the adult group, and 10 +/- 2 and 9 +/- 2 years in children. Among the whole group, 44% had tremor, 24% dystonia, 12% pure gait disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 12 publications
(40 reference statements)
1
35
0
1
Order By: Relevance
“…Recent reports have highlighted the occurrence of PMDs in children; these are largely similar to those seen in adults, although some differences may exist including possibly more frequent involvement of the dominant limb19 and less frequent coexisting organic neurological disease19 and underlying psychiatric disease 20. PMDs seen in other cultures, including Turkey21 and Spain,22 are largely similar to those found in North America. There is an extensive literature highlighting the considerable disability experienced by patients with conversion disorders, but little data exists directly related to PMDs.…”
Section: Advances In the Past 25 Yearsmentioning
confidence: 78%
“…Recent reports have highlighted the occurrence of PMDs in children; these are largely similar to those seen in adults, although some differences may exist including possibly more frequent involvement of the dominant limb19 and less frequent coexisting organic neurological disease19 and underlying psychiatric disease 20. PMDs seen in other cultures, including Turkey21 and Spain,22 are largely similar to those found in North America. There is an extensive literature highlighting the considerable disability experienced by patients with conversion disorders, but little data exists directly related to PMDs.…”
Section: Advances In the Past 25 Yearsmentioning
confidence: 78%
“…In contrast, Thomas et al, evaluated 228 patients with PMD with a mean follow-up of 3.4 years (6 months to 12 years), and concluded that symptoms improved in 56.6% of patients, worsened in 22.1% and remained the same in 21.3% 42 . Ertan et al studied 49 patients with PMD in a tertiary clinic in Turkey and concluded that the response to treatment was poor, with a high rate of drop out of these patients in the follow-up 44 .…”
Section: Prognosis Of Pmdmentioning
confidence: 99%
“…In other series, the frequency of PSVDs in patients with PMDs varies between 3.6 and 28 % ( Table 2) [9][10][11][12][13][14][15][16][17]. Although abnormal speech has been proposed in a rating scale for PMDs, highlighting the importance of this manifestation, many case series of PMDs do not mention the presence of speech or voice disorders and the descriptions often lack detail.…”
Section: Discussionmentioning
confidence: 92%